(untitled) (Medical Forum Monthly, 2024)
Objective: To observe the antioxidant effect of vitamin E on the toxicity of doxorubicin of rat testes. Study Design: Analytical experimental randomized control study Place and Duration of Study: This study was conducted at the Department of Anatomy, Peshawar Medical College Peshawar from February 2013 to July 2013. Materials and Methods: Thirty two rats were randomly divided into two main groups; normal and the experimental groups. Experimental group was further divided into the toxic and vitamin E groups. The toxic group (B-I) was given doxorubicin at the dose of 2 mg/kg body weight, i.e. weekly for four weeks. While the vitamin E group (B-II) was introduced with the oral administration of vitamin E at the dose of 150 mg/kg daily for four weeks along with the doxorubicin i.e. weekly for four weeks. After scarifying the animal according to the protocol the testis were sectioned and then preparatory slides were used to apply the basic stains i.e. H and E stain, PAS stain and Massan Trichrome stains. Results: Group B-I treated with Doxorubicin only showed marked decreased in body weight, testicular weight, decreased height of epithelium and germ cells count as compared to B-II. Conclusion: The simultaneous use of vitamin E as an antioxidant, can protect the toxic effects of Doxorubicin and thus damage to the testes.